1997
DOI: 10.1073/pnas.94.6.2513
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent hemopoietic stem cells are c-kit <low

Abstract: Pluripotent hemopoietic stem cells (P-HSCs) were thought to be c-kit ؉ , but recent reports indicate that they are c-kit low . In the present report, we provide evidence using Ly5 congenic mice that P-HSCs are c-kit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 29 publications
3
59
1
Order By: Relevance
“…12,13,16 It is well documented that the c-kit/SCF system plays an important role in the early stage of hematopoiesis. 23,26,32,[37][38][39][40][41][42] Therefore, it is important to clarify the pattern of c-kit expression on primitive stem/progenitor cells, but there have been conflicting reports concerning this antigen on such cells. It was reported that LTC-IC and cell cycle dormant progenitors and blast cell colony-forming cells are enriched in the human BM-and CB-derived CD34 + c-kit low cell populations, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,16 It is well documented that the c-kit/SCF system plays an important role in the early stage of hematopoiesis. 23,26,32,[37][38][39][40][41][42] Therefore, it is important to clarify the pattern of c-kit expression on primitive stem/progenitor cells, but there have been conflicting reports concerning this antigen on such cells. It was reported that LTC-IC and cell cycle dormant progenitors and blast cell colony-forming cells are enriched in the human BM-and CB-derived CD34 + c-kit low cell populations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Katayama et al 40 proposed a model in which c-kit expression progresses from low levels on primitive progenitors to high levels on actively cycling progenitors. Very recently, Doi et al 41 clearly demonstrated that pluripotent hematopoietic stem cells with long-term repopulating activity are lin − /CD71 − /classI high /ckit Ͻlow cells but not lin − /CD71 − /c-kit low cells. They defined these cells, which appeared to be c-kit − on FACS analysis, as c-kit Ͻlow cells.…”
Section: Figurementioning
confidence: 99%
“…We prepared partially purified stem cell-enriched BMCs as previously described [26][27][28]. Briefly, 5-fluorouracil (Kyowa Hakko Kogyo; Tokyo, Japan) was injected into the peritoneal cavity of 4-week-old male Brown Norway rats (Clea Japan; Osaka, Japan) at 150 mg/kg body weight 48 hours before sacrifice.…”
Section: Preparation Of Stem Cell-enriched Bmcs For Graftingmentioning
confidence: 99%
“…Expression of FcR was considered because it has been observed on immature, antigencapturing DC (6). Cells also were stained for c-kit, a marker of early hemopoietic cells (20). Murine fetal liver-derived lin Ϫ ckit ϩ hemopoietic progenitor cells have been shown to develop into DC (21).…”
Section: Nonadherent Cells Produced In Ltc Represent Two Major Subsetsmentioning
confidence: 99%